含克拉屈滨预处理方案异基因造血干细胞移植治疗12例难治/复发急性髓系白血病临床观察 (Zhonghua Xue Ye Xue Za Zhi, 2019)
OBJECTIVE: To investigate the safety and efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) containing cladribine sequential busulfan regimen for refractory/relapsed acute myeloid leukemia (AML). METHODS: The clinical data of 12 refractory/relapsed AML patients received allo-HSCT with cladribine sequential busulfan regimen. RESULTS: ①Of the 12 patients, 9 were males and 3 females, with a median age of 36 (27–50) years. The donors were identical sibling (3), matched unrelated (1) and haploidentical family member (9) respectively. Nine patients reached partial remission and other remained no remission after chemotherapy before allo-HSCT. The median previous chemotherapy courses before allo-HSCT were 6 (2–13). ②Conditioning regimen: Smostine 250 mg·m(−2)·d(−1), d−7; Cladribine 5 mg·m(−2)·d(−1), d−6 to d−2; Cytarabine Arabinoside 2 g·m(−2)·d(−1), d−6 to d−2; Busulfan 3.2 mg·m(−2)·d(−1), d−6 to d−3; Rabbit anti-human thymocyte immunoglobulin (ATG) 1.5 mg·m(−2)·d(−1) (unrelated donor transplantation) or 2.0–2.5 mg·m(−2)·d(−1) (haplo-HSCT), d−4 to d−1. ③Of the 12 patients, 11 patients attained complete haploidentical engraftment, one case occurred primary graft failure. The median durations for neutrophils and platelet implantations were 15 (15–21) and 19 (17–30) days respectively. ④After conditioning, no hepatic veno-occlusive diseases were observed, hemorrhagic cystitis occurred in 2 patients, 8 patients had fever, 3 cases experienced acute GVHD grade II, localized chronic GVHD occurred in 8 patients. ⑤The median follow-up was 8 (4–12) months. Leukemia relapse occurred in 2 patients at time of 6, 12 months after allo-HSCT. The estimated 1-year OS and DFS were (71.1±1.8) % and (62.2±1.8) %, respectively. CONCLUSION: allo-HSCT with cladribine sequential busulfan regimen was a feasible choice with favorable outcome for refractory/relapsed AML.